Obestatin improves ischemia/reperfusion-induced renal injury in rats via its antioxidant and anti-apoptotic effects: Role of the nitric oxide - YEGEN, BERRAK; KOÇ, MEHMET; ÖZKAN YENAL, NAZİYE; ÇETİNEL, ŞULE; ÖZDEMİR KUMRAL, ZARİFE NİGAR (ELSEVIER SCIENCE INC, 2014)
Obestatin was shown to have anti-inflammatory effects in several inflammatory models. To elucidate the potential renoprotective effects of obestatin, renal I/R injury was induced in male Sprague Dawley rats by placing a clamp across left renal artery for 60 min following a right nephrectomy. Clamp was released and the rats were injected with either saline or obestatin (10, 30, 100 mu g/kg). In some experiments, obestatin (10 mu g/kg) was administered with L-NAME (10 mg/kg) or L-Nil (0.36 mg/kg). Following a 24-h reperfusion, the rats were decapitated to measure serum creatinine and nitrite/nitrate levels, renal malondialdehyde (MDA), glutathione (GSH) levels and myeloperoxidase (MPO) activity and to assess cortical necrosis and apoptosis scores. Obestatin treatment reduced I/R-induced increase in creatinine levels, renal MPO activity and renal MDA levels, while renal GSH levels were significantly increased by obestatin. Histological analysis revealed that severe I/R injury and high apoptosis score in the kidney samples of saline-treated rats were significantly reduced and the cortical/medullary injury was ameliorated by obestatin. Expression of eNOS, which was increased by I/R injury, was further increased by obestatin, while serum NO levels were significantly decreased. iNOS inhibitor L-Nil reduced oxidative renal damage and improved the functional and histopathological parameters. I/R-induced elevation in eNOS expression, which was further increased by obestatin, was depressed by L-NAME and L-Nil treatments. The present data demonstrate that obestatin ameliorates renal I/R-injury by its possible anti-oxidative, anti-inflammatory and anti-apoptotic properties, which appear to involve the suppression of neutrophil accumulation and modulation of NO metabolism. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: Obestatin; Renal ischemia-reperfusion injury; Nitric oxide; Oxidative stress; ISCHEMIA-REPERFUSION INJURY; CELL INJURY; IN-VIVO; FAILURE; GHRELIN; DYSFUNCTION; ATTENUATION; MECHANISMS; SYNTHASE; KIDNEY